TINJAUAN LITERATUR MENGENAI NILAI-NILAI AKHLAK DALAM AL-QUR’AN DAN KONTRIBUSINYA TERHADAP PENDIDIKAN - Rachel Amalia; Hesti Rahamwati; Yuniy Sarah Hasibuan; Nurul Hikmah; Nurhidayah; Sangkot Abdullah Efendi Harahap (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study was motivated by the weakening internalization of moral values in education, which has an impact on students' personal and social behavior. The purpose of this study is to examine the moral values contained in the Qur'an and analyze their contribution to character building in the context of Islamic education. The research method used is qualitative research with a library research approach, through a review of primary and secondary sources in the form of the Qur'an, tafsir books, books, and scientific articles relevant to the research theme. The data were analyzed using descriptive-analytical techniques to identify the main moral values in the Qur'an, such as compassion, honesty, justice, responsibility, mutual respect, and social sensitivity, as well as their relevance in educational practice. The results of the study show that the Qur'an places moral education as the main foundation in shaping people who are faithful, knowledgeable, and have noble personalities. Qur'anic moral values are not only normative but also applicable and can be implemented through integration in learning, educator role modeling, habituation, and school culture. Thus, strengthening Qur'an-based moral education has a strategic role in shaping the character of students who are honest, ethical, and responsible in social life.